Photoelectron spectroscopy and theoretical studies of PCSe- , AsCS- , AsCSe- , and NCSe-: insights into the electronic structures of the whole family of ECX- anions (E=N, P, As; X=O, S, Se) - Yuan, Q; Tambornino, F; Hinz, A; Borden, WT; Goicoechea, JM; Chen, B; Wang, X-B (Wiley, 2019)
The newly synthesized phosphorus‐ and arsenic‐containing analogues of the thio‐ and seleno‐cyanate anions, PCSe−, AsCS−, and AsCSe−, as well as the known ion NCSe− were investigated in the gas phase by negative‐ion photoelectron spectroscopy (NIPES), velocity‐map imaging (VMI) spectroscopy, and quantum‐chemical computations. The electron affinities (EA), spin–orbit (SO) splittings, and “symmetric”/“asymmetric” stretching frequencies of the neutral radicals ECX. (E=N, P, As; X=S, Se), generated by electron detachment from the corresponding anions, were obtained from the spectra. The calculated EAs, SO splittings, and vibrational frequencies are in excellent agreement with the experimental measurements. These newly obtained values, when combined with those previously determined for the lighter analogues, show interesting trends on descending the pnictogen and chalcogen series. These trends are rationalized based on electronegativity arguments, the electron distributions in the HOMOs, and NBO/NRT analyses.